Impact of digital payments on monetary policy transmission in India: evidence from the post-demonetization era - Mostafa, Husam; Arumugasamy, Duraisamy (Frontiers in Human Dynamics, 2025)
This study evaluates the impact of digital payments on monetary policy transmission in India post-demonetization. Using the Long Run ARDL Model, ARDL Short-Run Dynamics, and ARDL Error Correction Model, we find a significant negative correlation between digital payments and the Weighted Average Lending Rate on Fresh Rupees Loans (WALRF), with a 1 percent increase in digital payments leading to a 0.43 percent reduction in WALRF. Short-run dynamics show immediate impacts, enhancing competitive pressures within the banking sector. The error correction term indicates that monthly corrections account for 23 percent of long-term equilibrium variances, highlighting the stabilizing effects of digital financial infrastructures. Robustness tests, including the Breusch-Godfrey Serial Correlation LM Test, Breusch-Pagan-Godfrey Heteroskedasticity Test, Bounds Test for Cointegration, and CUSUM (Cumulative Sum) of squares test, confirm the results' reliability. The study advocates for promoting and integrating digital payment systems to enhance banking sector responsiveness and achieve broader macroeconomic goals.JEL codes: E4, E5